Hazard Identification, Risk Assessment, and Risk Control using HIRARC Methdod Analysis - Yovani Rehuel Br Sitepu; Jesica Natalia Simanungkalit (Jurnal Penelitian Perawat Profesional, 2020)
Industrial development in Indonesia, especially palm oil mill, must also be accompanied by occupational health and safety so as not to endanger workers. Occupational health and safety is needed to avoid work accidents in mills. The palm oil mill, whic is located in North Sumatera province, has been operating since 2010. This palm oil isn't separated form work accidents, although these accidents don’t interfere with work days and the work environment. The purpose of this research to avoid the occurance of a work accident in palm oil mills which can be done by identifying and assessing the hazards that occur in the factory. This research was conducted with a qualitative descriptive approach and analyzed using the HIRARC method, that are hazards identification, risk assessment, and risk control. Data obtained from the results of interviewing workers at palm oil mills.The results obtained are chemical and physical hazard potential with 21 risk factors and 21 possible work accidents. And the result obtained were 86% had moderate risk hazards and 14% had high risk hazards. Activities that have high risk hazards consist of 3, that are the explosion of the boiler in the room boiler, noise in palm kernel processing, and noise in crossed palm oil processing.